Intra‐abdominal vascularized lymph node transfer for treatment of lymphedema: A systematic literature review and meta‐analysis. Issue 8 (25th September 2021) - Li, Yunzhu; Dong, Ruijia; Li, Zhujun; Wang, Liquan; Long, Xiao
Abstract: Background: As a promising treatment for lymphedema, vascularized lymph node transfer (VLNT) is associated with a risk of iatrogenic lymphedema. Intra‐abdominal vascularized lymph node flap has been increasingly applied to minimize complication. Methods: PubMed, EMBASE, Web of Sciences, and Cochrane databases were searched systematically. Clinical articles describing the application of intra‐abdominal flaps to treat lymphedema were included. Study characteristics, patient demographics, and operative details were recorded. Primary outcomes were recorded as circumference/volume reduction, episodes of cellulitis reduction and lymph flow assessment. Secondary outcomes were recorded as donor‐site complication and recipient‐site complication. Results: Twenty‐one studies met the inclusion criteria with 594 patients in total. Donor‐sites of flaps were omental/gastroepiploic, jejunal, ileocecal, and appendicular. The mean reduction rate ranged from 0.38% to 70.8%. Significant reduction in infectious episodes was reported in 10 studies. The pooled donor‐site complication rate was 1.4% (95% CI, 0%–4.1%; I 2 = 40%). The pooled recipient‐site complication rate was 3.2% (95% CI, 1.4%–5.5%; I 2 = 39%). The most common donor‐site complication was minor ileus requiring prolonged nasogastric tube replacement. No donor site lymph disfunction occurred. Conclusion: Intra‐abdominal VLNT is an effective technique for patients with lymphedema with no obvious impairment to donor‐site lymph function, as long as the operation is properly performed.